Assistance in the Adoption of the Kurikulum Merdeka at Elementary School 1 Padokan Yogyakarta - Supartinah, Supartinah; Prananto, Irfan Wahyu; Kawuryan, Sekar Purbarini; Hastomo, Agung; Senen, Anwar (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity program aims to increase partner schools' capacity to welcome the implementation of the independent curriculum at Padokan 1 Public Elementary School. The methods for implementing community service activities were workshops and assistance in product preparation. The products developed were Formulation of Learning Objectives Flow (ATP) and Learning Objectives (TP), learning modules, and assessment sheets. The target of the activity was sixteen teachers at Padokan 1 Elementary School. The analysis started with the program's preparation, implementation, and evaluation. The results of this activity program were the Learning Objectives (ATP) and Learning Objectives (TP) Flowcharts, learning modules, and assessment sheets. The results showed that this program was feasible and follows the needs of the target schools. Teachers at partner schools at least had an idea of what to do in welcoming the implementation of the independent curriculum at partner schools. The set was well structured as a product of the training. Thus, the partner schools at least have the confidence to welcome the implementation of the independent curriculum.